2009
DOI: 10.1007/s10157-009-0227-x
|View full text |Cite
|
Sign up to set email alerts
|

An IgA1-lambda-type monoclonal immunoglobulin deposition disease associated with membranous features in a patient with chronic hepatitis C viral infection and rectal cancer

Abstract: A 61-year-old man infected with hepatitis C virus developed urinary protein. Two-dimensional electrophoresis and immunoblotting of sera revealed no monoclonal proteins. Light microscopy and immunofluorescence of a kidney biopsy specimen demonstrated bubbling appearance and formation of spikes, associated with predominantly IgA1-lambda deposition, but not IgG, along glomerular capillary walls. Electron microscopy showed electron-dense deposits without any fibrillary structure located in the glomerular basement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Komatsuda et al [5] reported three cases (two IgG3-j and one IgG1-j) of membranous nephropathy. Recently, Miura et al [6] reported a rare case of membranous nephropathy with IgA1-k deposition along the glomerular peripheral wall in a patient with chronic hepatitis C infection and rectal cancer. Differences between types of mIg deposition and in affinity for the glomerulus remain uncharacterized in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Komatsuda et al [5] reported three cases (two IgG3-j and one IgG1-j) of membranous nephropathy. Recently, Miura et al [6] reported a rare case of membranous nephropathy with IgA1-k deposition along the glomerular peripheral wall in a patient with chronic hepatitis C infection and rectal cancer. Differences between types of mIg deposition and in affinity for the glomerulus remain uncharacterized in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…AL amyloidosis, light and/or heavy chain deposition disease (i.e., LCDD, LHCDD, HCDD, respectively) and organized type MIDD (i.e., immunotactoid glomerulopathy, fibrillary glomerulonephritis, and type-1 cryoglobulinemia) have been widely recognized. Recently, other types of MIDD glomerulopathy (i.e., non-AL amyloid and non-LCDD/LHCDD/HCDD, nonorganized) have been reported in the literature [1][2][3][4][5][6]. However, circulating mIg is not typically associated with renal involvement, and all forms of MIDD are related to the expansion of a B cell clone-producing mIg.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with HCV is associated with various renal diseases including membranoproliferative GN, cryoglobulinemic GN, fibrillary GN, immunotactoid GN, and lightchain (AL) amyloidosis [15,25,26]. In addition, monoclonal IgA1λ-type immunoglobulin deposition disease was recently reported in a patient with HCV infection [27], and we reported a case of PGNMID with monoclonal IgG1λ deposits in a patient with HCV infection [28]. We speculate based on our cases and the other PGNMID cases in patients with HCV or parvovirus B19 infection that immune disorders after virus infection may be associated with PGNMID pathogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Two of the previously reported cases of IgA-type monoclonal immunoglobulin deposition disease (MIDD) involved membranous features (2,3). For example, Sethi reported a case of membranous nephropathy associated with monoclonal IgA-kappa deposits and crescents (2), while Miura et al reported a case of chronic hepatitis C viral infection and rectal cancer that presented with IgA1-lambda-type membranous deposition on a renal biopsy (3).…”
Section: Discussionmentioning
confidence: 99%